PROBLEMATICS AND TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION EVALUATION MANAGEMENT IN THE DIGITAL ERA: A SYSTEMATIC REVIEW OF THE LITERATURE THEORY OF EDUCATIONAL MANAGEMENT TONY BUSH 2008 - Moch. Salman Alfarizi; Muhamad Ali; Adiba Maulidiyah (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Digital transformation in the world of education has brought significant changes to the Islamic Religious Education (PAI) learning evaluation system, especially through the use of e-assessment, Learning Management System (LMS), artificial intelligence, and various digital platforms in the learning assessment process. These conditions present various opportunities in increasing the effectiveness and efficiency of learning evaluations, as well as raising problems related to teachers' digital competence, the limitations of technological infrastructure, and difficulties in measuring the affective and spiritual aspects of students digitally. This research aims to analyze the problems, transformations, and strategies for the development of Islamic Religious Education evaluation management in the digital era through a systematic review of the literature. The study uses a qualitative approach using the Systematic Literature Review (SLR) method on articles from accredited national journals and reputable international journals in the 2021–2026 range obtained through Google Scholar, Scopus, Garuda, and Dimensions databases. The results showed that the transformation of PAI digital evaluation had a positive impact on learning effectiveness, assessment transparency, and efficiency of processing evaluation results. The implementation of digital evaluation still faces challenges, including low digital literacy of teachers, limited access to technology, weak development of digital-based spiritual evaluation, and the lack of optimal integration of Islamic values in the modern evaluation system. The development of PAI evaluation management in the digital era requires strengthening teachers' digital competence, developing authentic evaluations based on Islamic values, supporting education policies, and equitable distribution of technological infrastructure to create an evaluation system that is adaptive, humanist, and still oriented towards the formation of students' character and spirituality.